More Evidence that Surgical Intervention for Unstable Distal Radius Fracture in Elderly Does not Offer a Superior Patient Perceived Functional Advantage over Time Honored Conservative Treatment in Long Term Follow-Up: A Critical Appraisal at 10 Years (Range 10–13 Years) Follow-up Study - Raghavendra S Kulkarni; Sriram R Kulkarni (Journal of Orthopaedic Case Reports)
Introduction: In this study, elderly distal radius fracture treatment by both conservatively and surgical intervention was examined at 1 and 2 years post-injury and then reevaluated after a median of 10 (range 10–13) years. Materials and Methods: Sindhudurg residents who were treated by the author for distal radius fracture between January 01st, 2008, to December 31st, 2011, at Government District Hospital Sindhudurg are enrolled in this prospective study. The follow-up clinic was conducted in the orthopedic department from January 01st, 2022, to May 31st, 2022, with a long-term follow of 10–14 years after this original study period of 2008–2011. The patients in the study period of 2008–2011 were treated by five different treatment methods, both operative and conservative. Results: The mean patient-rated wrist evaluation score was 12 (standard deviation [SD] = 17, range 0–96). The mean EuroQol Visual Analog Scale was 81.2 (range 25–100, 95% confidence interval 76–84). The scores were lower in patients treated conservatively compared to three subgroups of surgical intervention (P = 0.03). The patient self-rated outcomes at long-term follow-up with mean ± SD values were for the surgical intervention group, pins and plaster 13.5 ± 29.6, external fixator 14.6 ± 32.1, open reduction, and internal fixation 6.3 ± 22.3. Similar values for conservatively treated patients were for below elbow cast 7.3 ± 12.5 and for above elbow cast with forearm in supination 7.2 ± 13.3, respectively. The conservatively treated patient group (mean ± SD, 11.5 ± 28.0 vs. 7.3 ± 12.9: P = 0.5) with better functional outcomes and greater satisfaction (P = 0.5) for the difference. Overall 36 (43.9%) elderly patients treated by the conservative method were very much satisfied with the eventual long-term outcome of their distal radius fracture as against 27 (35.5%) treated by surgical intervention. Similarly, 4 (4.8%) were very much dissatisfied in the conservatively treated group as against 10 (15.7%) from the surgical intervention group (P > 0.001). Discussion: Conservative treatment has always been a dilemma for surgeons. Indeed, the quality of anatomic reduction assessed on radiographs is often recognized as a predictive factor for a good functional result; however, several studies proved that this dogma was disputable. Despite wrist arthritis, the functional result is not different. A systematic review of the literature and meta-analysis comparing conservative treatment and surgical intervention found similar results. Conclusion: Elderly patients treated conservatively had overall long-term better functional outcomes and patient satisfaction with improved patient-reported daily living activities than patients treated by surgical intervention.